2018
DOI: 10.1371/journal.pone.0203879
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis-associated hepatocarcinogenesis revisited: Establishing standard medium-term chemically-induced male and female models

Abstract: Hepatocellular carcinoma causes ~10% of all cancer-related deaths worldwide, usually emerging in a background of liver fibrosis/cirrhosis (70%-90% of cases). Chemically-induced mouse models for fibrosis-associated hepatocarcinogenesis are widely-applied, resembling the corresponding human disease. Nonetheless, a long time is necessary for the development of preneoplastic/neoplastic lesions. Thus, we proposed an early fibrosis-associated hepatocarcinogenesis model for male and female mice separately, focusing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Chemical carcinogens commonly used to mimic HCC in rodent models induce HCC either selectively or much more aggressively in males. As a result, studies of HCC in females have been fewer, although progress is being made to model the disease in both sexes (61). Our data provide mechanistic insight into the association of lipid metabolism dysregulation and HCC risk for both sexes, an association that will likely be important in the decades to come, considering the prevalence of NAFLD and its association with HCC development.…”
Section: Discussionmentioning
confidence: 91%
“…Chemical carcinogens commonly used to mimic HCC in rodent models induce HCC either selectively or much more aggressively in males. As a result, studies of HCC in females have been fewer, although progress is being made to model the disease in both sexes (61). Our data provide mechanistic insight into the association of lipid metabolism dysregulation and HCC risk for both sexes, an association that will likely be important in the decades to come, considering the prevalence of NAFLD and its association with HCC development.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, DEN-induced C57BL/6J mice liver cancer model was used to simulate the development of human HCC in vivo. 27 We found that the expression of GRK2 gradually decreased when the degree of malignancy increased, while there was no significant change in GRK3 expression. In vitro, GRK2 expression was obviously decreased in HCCLM3 and MHCC97H cell lines with high metastatic potential than in SMC7721 and HepG2 cell lines with low metastatic potential.…”
Section: Discussionmentioning
confidence: 65%
“…The liver-cancer susceptible C3H/HeJ mice strain was submitted to a previously established fibrosis-associated hepatocarcinogenesis model [11]. Briefly, male mice (n = 5 to 10 animals/group) were initiated for liver carcinogenesis by receiving a single intraperitoneal (i.p.)…”
Section: Experimental Designmentioning
confidence: 99%
“…(corresponding to 0.025 µL/g or 0.040 µg/g of pure CCl4) and there were 0.25 µL weekly increments to the utmost dose of 1.50 µL/g b.wt. (corresponding to 0.15 µL/g or 0.24 µg/g of pure CCl4) [11]. In addition, from week 7 to 17, mice received CAF alone (50 mg/kg b.wt.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation